Illegal Fishing di Perairan Indonesia: Permasalahan Dan Upaya Penanganannya Secara Bilateral di Kawasan Asia Tenggara - Maria Irawati Banafanu; Yulyana Crykid Sili Mudamakin; Yohanes Arman (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Illegal fishing still frequently occurs in Indonesian waters although many efforts have been conducted to stop it. Illegal fishing is not a typical problem Indonesia facing since it experienced also by other rich resource-countries due to its nature as a transnational crime. The writer therefore argues that the solution to overcome such transitional crime shall be done through a cross-national cooperation, including through a bilateral one. Although cooperation with neighboring countries have been conducted by Indonesia, multilateral- and bilaterally, however, all these still cannot secure the waters from illegal fishing. That is why a more serious and a better cooperation, in particular bilaterally, must be fostered by Indonesia’s government to effectively counter such a transnational crime. This research report discusses illegal fishing in the Indonesian waters, its causes, and the ways to handle it so far in the region.